2014
DOI: 10.1039/c3cc48695h
|View full text |Cite
|
Sign up to set email alerts
|

A bis(2-oxoindolin-3-ylidene)-benzodifuran-dione containing copolymer for high-mobility ambipolar transistors

Abstract: A bis(2-oxoindolin-3-ylidene)-benzodifuran-dione (BIBDF)-based low band gap polymer (PBIBDF-BT), containing a solubilizing alkyl chain bithiophene unit as a donor, has been synthesized. The polymer with a low-lying LUMO/HOMO energy level (-4.03/-5.55 eV) exhibits efficient ambipolar charge transport. The electron and hole mobilities are as high as 1.08 and 0.30 cm(2) V(-1) s(-1), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 35 publications
(4 reference statements)
0
57
0
Order By: Relevance
“…Polymer materials with advantages of superior viscosity, thermal, mechanical and simple processing characteristics have been proverbially employed in photovoltaics (PV), transistors, light‐emitting diodes, logic circuits, sensors, etc . Particularly, D–A polymers that possess noncovalent intramolecular interactions for efficient π‐conjugation and close stacking ensuring intermolecular charge hopping have been extensively investigated . The conjugated polymers consisting of donors including selenophenes and thiophenes and acceptors comprising DPPs, NDIs, isoindigos, thiadiazolopyridine, naphthalenedicarboximide, and benzothiadiazole are mainly synthesized via Stille, Suzuki, and direct arylation polycondensation.…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…Polymer materials with advantages of superior viscosity, thermal, mechanical and simple processing characteristics have been proverbially employed in photovoltaics (PV), transistors, light‐emitting diodes, logic circuits, sensors, etc . Particularly, D–A polymers that possess noncovalent intramolecular interactions for efficient π‐conjugation and close stacking ensuring intermolecular charge hopping have been extensively investigated . The conjugated polymers consisting of donors including selenophenes and thiophenes and acceptors comprising DPPs, NDIs, isoindigos, thiadiazolopyridine, naphthalenedicarboximide, and benzothiadiazole are mainly synthesized via Stille, Suzuki, and direct arylation polycondensation.…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…Several p‐type or n‐type organic semiconductors, such as pentacene, dialkyl tetrathiapentacene (DTBDT‐C6), poly(3‐hexylthiophene) (P3HT), copper phthalocyanine (CuPc), and naphthalene diimides fused with 2‐(1,3‐dithiol‐2‐ylidene)malonitrile groups (NDI(2OD)(4tBuPh)‐DTYM2), have been used as materials for chemical gas sensors with varying sensing properties towards analyte species, including NH 3 , SO 2 , NO 2 , dimethyl methylphosphonate (DMMP), H 2 O 2 , acetone, toluene, and halothane. In the present study, a previously reported donor–acceptor (D–A), conjugated, low bandgap polymer based on bithiophene and bis(2‐oxoindolin‐3‐ylidene)‐benzodifuran‐dione (BIBDF), namely PBIBDF‐BT (Figure b), is used as an active layer of the transistor. A continuous PBIBDF‐BT film could generally be obtained through spin coating of a single‐component PBIBDF‐BT solution on silicon substrates.…”
mentioning
confidence: 99%
“…To pursue high mobility, many new conjugated polymers have been designed and synthesized, and encouraging progress has been made with hole mobility of OTFTs up to 10 cm 2 V À1 s À1 and electron mobilities over 1 cm 2 V À1 s À1 in the past few years [4][5][6][7][8]. Solution processable conjugated polymers generally contain two parts: p-conjugated backbone and flexible solubilizing side chains.…”
Section: Introductionmentioning
confidence: 99%